“Diseño geométrico, estructural y drenaje pluvial de las calles de la ciudadela la libertad, y de la lotización los álamos, perteneciente al cantón arenillas, provincia de el oro, año 2014” - Alvarado Mendoza, Julio César (2015)
At Citadel Freedom and lotización Los Alamos there is a need for studies to the geometric design, structural and storm sewer main and secondary roads, as these in its currently in poor condition, there is no proper planning of their streets, shows that you do not have curbs, gutters, sewers; Its wide roads are not well defined making it difficult for both vehicular and pedestrian traffic, being necessary to carry out this project, and bearing in mind the current concerns in which the inhabitants of this citadel and lotización live. In order to help the inhabitants of the citadel and lotización, one of the major problems faced, which is the bad states of its tracks. With the completion of the studies and designs of the streets of the citadel Liberty, and lotización Los Alamos, belonging to the Canton Arenillas, El Oro province, aims to prevent and reduce damage caused by rains in the winter , since the lack of storm drains causes the first downpours route becomes impassable obstacles by forming or deep furrows that restrict the movement to larger vehicles as for cars it is almost impossible. With the completion of this project the beneficiaries would be the inhabitants of the citadel La Libertad and lotización Los Alamos, because that can market their products with much more freedom and they will not have any obstacles to mobilize, vehicular or peatonalmente by its tracks. Since the population says that during the winter the road becomes almost impassable so is hampered output of agricultural products from these sites to the places of sale, since all they ask is improving and ease vehicular traffic and pedestrian All this constitutes the pillars of the family economy and paralyzed by the poor condition of the road produces backwardness and poverty to its inhabitants and further reduction of infectious diseases by accumulation of pools of water. The proposal for this project is currently in force since the inhabitants of the sectors which will benefit, ask urgently work paving their way to work and mobilize the products they cultivate their lands are made . An alternative is to provide a solution to this problem that wreaks havoc to the inhabitants of the citadel of freedom and lotización poplars, to conduct studies and designs necessary to apply all my knowledge to achieve placate something dissatisfactions that have said inhabitants. Traductor de Google para empresas:Google Translator ToolkitTraductor de sitios web